(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
This article presents some ideas about the existing problems in teaching English to school-age children and their solutions. The article also presents some ideas about educational approaches, interactive methods, and game technologies that are considered effective in teaching English to school-age children.